New species and records of Diaporthe from Jiangxi Province, China - Yang, Qin (MycoKeys, 2021)
Diaporthe species have often been reported as important plant pathogens, saprobes and endophytes on a wide range of plant hosts. Although several Diaporthe species have been recorded, little is known about species able to infect forest trees in Jiangxi Province. Hence, extensive surveys were recently conducted in Jiangxi Province, China. A total of 24 isolates were identified and analysed using comparisons of DNA sequence data for the nuclear ribosomal internal transcribed spacer (ITS), calmodulin (cal), histone H3 (his3), partial translation elongation factor-1α (tef1) and β-tubulin (tub2) gene regions, as well as their morphological features. Results revealed five novel taxa, D. bauhiniae, D. ganzhouensis, D. schimae, D. verniciicola, D. xunwuensis spp. nov. and three known species, D. apiculatum, D. citri and D. multigutullata.